Optimizing Students' Critical Thinking and Communication Skills Through Discovery Learning - Marlina Marlina; Nadia Aldyza; Afkar Afkar (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2025)
This study aims to describe the implementation of the Discovery Learning model and its impact on the development of students’ critical thinking and communication skills in the topic “Understanding Animal Life Cycles” for third-grade students at SD Negeri Kampung Besar. This research employed a descriptive qualitative approach, collecting data through observations, interviews, and documentation. All data were systematically analyzed using NVivo software to strengthen the coding process and thematic interpretation. The findings show that Discovery Learning creates a more active and meaningful learning environment through exploration, discussion, concept discovery, and reflection. Students became more engaged in independently constructing their understanding of animal life cycle stages, resulting in better comprehension and retention. Additionally, the model enhanced students’ critical thinking skills, particularly in distinguishing types of metamorphosis and providing logical, independent reasoning. Communication skills also improved through group discussions and presentations. Overall, Discovery Learning effectively increased students’ motivation, active participation, and learning effectiveness while strengthening essential 21st-century skills in elementary school learners.